Formula Tari Modinggu pada Masyarakat Tolaki Di Desa Benua Utama Kecamatan Benua Kabupaten Konawe Selatan - Dian Ardianti; Abdul Alim; Salniwati Salniwati (LISANI: Jurnal Kelisanan, Sastra, dan Budaya, 2022)
The purpose of this study was to determine and explain the Modinggu dance formula in Benua Utama Village, Benua District, South Konawe District and to know and explain the pattern of inheritance of Modinggu dance for Tolaki people in Benua Utama Village, Benua District, South Konawe District. Methodologically, this study uses a qualitative descriptive approach where information data is collected through observation, interviews, and documentation. The results of this study indicate that: Modinggu dance formula in Benua Utama Village, Benua Subdistrict, Konawe Selatan District is played: as a means of entertainment, as a means of traditional ceremonies, and as a means of performance. Nevertheless some of the dance formulas of the week to the Tolaki tribal community will certainly provide a container for the performance of the Modinggu dance after the rice harvest party to the Tolaki tribal community, as has become the custom of the community. The pattern of inheritance of Modinggu dance for Tolaki people in Benua Utama Village, Benua District, South Konawe Regency covers, family environment, education, and community. Nevertheless the Modinggu dance formula is inherently inherited by the Tolaki tribe community both family, education and community environment in order to preserve the traditional Tolaki dance for the younger generation.